2018
DOI: 10.1186/s12896-018-0484-4
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of nutrients removal from brewery wastewater using a hydroponic technology with Typha latifolia

Abstract: BackgroundThis study aims to assess suitability of hydroponic technology for treatment of brewery wastewater in a hydroponic bioreactor using Typha latifolia. Triplicated hydroponic bioreactor treatment units were designed, constructed and operated at a hydraulic retention time of 5 days with different surface loadings and mean hydraulic loading rate 0.023 m3 m−2d− 1. Young T. latifolia shoots were collected in the vicinity of study site. Wastewater characteristics, plant growth and nutrient accumulation durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In general, TP treatment efficiency tends to increase with sampling times, the highest efficiency is 76% (Colocasia esculenta) and 74% (Caladium bicolor) and only about 29% compared to the blank model. The results are similar with the result of [21] treatment brewery wastewater with Typha latifolia.…”
Section: The Variation Of Total Nitrogen (Tn) Removal Efficiencysupporting
confidence: 88%
See 2 more Smart Citations
“…In general, TP treatment efficiency tends to increase with sampling times, the highest efficiency is 76% (Colocasia esculenta) and 74% (Caladium bicolor) and only about 29% compared to the blank model. The results are similar with the result of [21] treatment brewery wastewater with Typha latifolia.…”
Section: The Variation Of Total Nitrogen (Tn) Removal Efficiencysupporting
confidence: 88%
“…To that end, biological processes are considered to play a major role. Bioremediation uses beneficial microorganisms [17][18][19] and plants [20][21][22][23] to degrade, reduce or detoxify pollutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [18] reported that the use of organic nutrient also serves to immobilize oil-degrading strains which consume these substrates and transform them into usable biomass for hydrogenase. However, the appreciable TPH removal efficiency of 58.39% recorded by treatments amended with BWW (BST-1) when compared to BST-5 (MWW) (56.62%) can be attributed to the high nutrient content present in brewery wastewater which accounts for the substantial microbial load in BWW [18][19][20][21][22], required for enhanced biodegradation of crude oil [18]. This also explains the slight variation in the removal efficiencies recorded with the mixed substrates (BST-2, 3 & 4) with an average removal efficiency of 49.05%.…”
Section: B Discussionmentioning
confidence: 99%
“…On the other hand, the removal efficiency of NO3was higher than those NH4 + and TP in this present study. High removal rate of NO3could be attributed to microorganisms break down inorganic nitrogen mostly through the process of denitrification which converts nitrate to nitrogen gas, resulting so in the removal of nitrate (Gebeyehu et al, 2018). Furthermore, the average pH of raw greywater was 8, which is the optimum pH level, to contribute the nutrient removal through ammonification, nitrification and (Lee et al, 2009).…”
Section: Raw Greywater and Treated Greywater Characteristicsmentioning
confidence: 99%